2015
DOI: 10.1117/1.jbo.20.1.015003
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-controlledin vivoocular exposure to 1090-nm radiation suggests that near-infrared radiation cataract is thermally induced

Abstract: Abstract. The damage mechanism for near-infrared radiation (IRR) induced cataract is unclear. Both a photochemical and a thermal mechanism were suggested. The current paper aims to elucidate a photochemical effect based on investigation of irradiance-exposure time reciprocity. Groups of 20 rats were unilaterally exposed to 96-W∕cm 2 IRR at 1090 nm within the dilated pupil accumulating 57, 103, 198, and 344 kJ∕cm 2 , respectively. Temperature was recorded at the limbus of the exposed eye. Seven days after expos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 8 publications
0
13
0
Order By: Relevance
“…Some authors claimed that hyperthermia induced by infrared radiation may lead to cataract formation (40,41), while Wolbarsht hypothesized that this process was not thermal but photochemically-induced (42). In a more recent publication, Yu et al performed in vivo experiments with rats and found that exposure to 197 W/cm 2 1090-nm infrared reflectrography (IRR) for eight seconds led to a temperature increase of 10 °C at the limbus and 26 °C near the retina, which induced cataract (43). However, Yu et al used a laser as a source for IRR, which contains more heat radiation.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors claimed that hyperthermia induced by infrared radiation may lead to cataract formation (40,41), while Wolbarsht hypothesized that this process was not thermal but photochemically-induced (42). In a more recent publication, Yu et al performed in vivo experiments with rats and found that exposure to 197 W/cm 2 1090-nm infrared reflectrography (IRR) for eight seconds led to a temperature increase of 10 °C at the limbus and 26 °C near the retina, which induced cataract (43). However, Yu et al used a laser as a source for IRR, which contains more heat radiation.…”
Section: Discussionmentioning
confidence: 99%
“…The second hypothesis suggests that cataract is the result of photochemical effects within the lens [31] . Results from a recent experimental study by Schulmeister et al [3] appear to support the heat-induced cataract hypothesis. Accordingly, cataract forms only when there is an increase in the temperature at the limbus of more than 8 °C.…”
Section: Discussionmentioning
confidence: 51%
“…Consequently, the majority of the experimental studies carried out on ocular heat transfer have been restricted to in vivo and ex vivo animal studies [1][2][3] , and donor human eyes obtained postmortem [4] ; both of which do not accurately represent the physiological conditions of the living human. Measurements carried out using infrared (IR) thermography have also been reported in the literature [5][6][7] .…”
Section: Introductionmentioning
confidence: 99%
“…One eye was exposed and the contralateral eye was kept not exposed as a control. 30 In all these exposures, the temperature at the limbus increased exponentially within a fraction of a minute to an asymptote below 8°C on the exposed side whereas there was no temperature increase on the contralateral side. Light-scattering measurements at 1 week after the exposure did not reveal any significant increase of forward light scattering in the exposed lens or any difference in forward light scattering between the lens from the exposed and the contralateral not exposed lens as measured quantitatively.…”
Section: Recent Experimental Investigation Of Near Irr Cataractmentioning
confidence: 99%